PERANCANGAN SISTEM PREDIKSI KEBUTUHAN STOK DARAH BAGI ORGANISASI NON PROFIT MENGGUNAKAN METODE FUZZY MAMDANI - Edi, Edi (Universitas Methodist Indonesia, 2023)
A non-profit organization is a nonprofit organization formed with the aim of providing assistance, and it does not seek profit in its activities. In addition to organizing blood donation campaigns, non-profit organizations often help hospitals in need of blood by providing the necessary blood supply through the Indonesian Red Cross (PMI). However, the problem faced is that the availability of blood stock is often depleted during urgent situations, resulting in the inability to fulfill the hospitals' blood requests. Therefore, as a solution to address the challenges faced by non-profit organizations, the development of an information system for predicting blood stock requirements is necessary to determine whether there is a need to replenish the blood stock in the following months. In this research, the developed blood stock prediction system implements the Fuzzy Mamdani method. The research results indicate that the Fuzzy Mamdani method, in predicting blood stock requirements, has achieved a satisfactory level of accuracy. Although a limited number of rules, specifically 24 rules, were processed, this method was able to provide predictions that closely approximated the actual requirements. However, it should be noted that the accuracy level can be further improved by adding more comprehensive rules and using a wider dataset.